2004
DOI: 10.1126/science.1104639
|View full text |Cite
|
Sign up to set email alerts
|

Clues from Fe Isotope Variations on the Origin of Early Archean BIFs from Greenland

Abstract: Archean rocks may provide a record of early Earth environments. However, such rocks have often been metamorphosed by high pressure and temperature, which can overprint the signatures of their original formation. Here, we show that the early Archean banded rocks from Isua, Akilia, and Innersuartuut, Greenland, are enriched in heavy iron isotopes by 0.1 to 0.5 per mil per atomic mass unit relative to igneous rocks worldwide. The observed enrichments are compatible with the transport, oxidation, and subsequent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
172
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 263 publications
(190 citation statements)
references
References 30 publications
13
172
3
2
Order By: Relevance
“…Using reduced isotopic partition function ratios for FeS 2 and Fe(II)-aquachloro complexes determined previously (Polyakov, 1997;Polyakov and Mineev, 2000;Schauble et al, 2001;Polyakov et al, 2007), the isotope fractionation factors  between FeS 2 and FeCl 4 2-or Fe(H 2 O) 6 2+ are ~1.0015 at 350°C. Although these positive fractionation factors are opposite to the kinetic isotope fractionation during FeS precipitation, either from Fe(II) aq solutions at room temperature (Butler et al, 2005) or from silicate melt at magmatic temperatures (Schuessler et al, 2007), it may explain the occurrence of positive A different interpretation involves sulphidisation of Fe-oxide minerals for the origin of these grains, as positive δ 56 Fe values have so far been described mainly from BIFs in the Archaean rock record Dauphas et al, 2004;Rouxel et al, 2005;Whitehouse and Fedo, 2007). Evidence for sulphidisation of Fe and Fe-Ti oxides, such as magnetite and ilmenite, collectively referred as "black sands", as well as BIF clasts has been observed in previous studies (Ramdohr, 1958) and resulted in a long-standing debate on the timing of sulphidisation, with the "placerists" arguing for pre-depositional sulphidisation (Ramdohr, 1958;Reimer and Mossman, 1990) and the "hydrothermalists" arguing for postdepositional sulphidisation of "black sands" (Barnicoat et al, 1997;Law and Phillips, 2006).…”
Section: Origin Of Rounded Pyrite With Highly Positive δ 56 Fe Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using reduced isotopic partition function ratios for FeS 2 and Fe(II)-aquachloro complexes determined previously (Polyakov, 1997;Polyakov and Mineev, 2000;Schauble et al, 2001;Polyakov et al, 2007), the isotope fractionation factors  between FeS 2 and FeCl 4 2-or Fe(H 2 O) 6 2+ are ~1.0015 at 350°C. Although these positive fractionation factors are opposite to the kinetic isotope fractionation during FeS precipitation, either from Fe(II) aq solutions at room temperature (Butler et al, 2005) or from silicate melt at magmatic temperatures (Schuessler et al, 2007), it may explain the occurrence of positive A different interpretation involves sulphidisation of Fe-oxide minerals for the origin of these grains, as positive δ 56 Fe values have so far been described mainly from BIFs in the Archaean rock record Dauphas et al, 2004;Rouxel et al, 2005;Whitehouse and Fedo, 2007). Evidence for sulphidisation of Fe and Fe-Ti oxides, such as magnetite and ilmenite, collectively referred as "black sands", as well as BIF clasts has been observed in previous studies (Ramdohr, 1958) and resulted in a long-standing debate on the timing of sulphidisation, with the "placerists" arguing for pre-depositional sulphidisation (Ramdohr, 1958;Reimer and Mossman, 1990) and the "hydrothermalists" arguing for postdepositional sulphidisation of "black sands" (Barnicoat et al, 1997;Law and Phillips, 2006).…”
Section: Origin Of Rounded Pyrite With Highly Positive δ 56 Fe Valuesmentioning
confidence: 99%
“…The c. 2.96 and 2.90 Ga magnetite-rich shales of the Witwatersrand Supergroup have also yielded predominantly negative δ 56 Fe values (-1.4 to 0.3 ‰; Yamaguchi et al, 2005). In contrast, Feoxides in Archaean BIFs are frequently characterised by positive δ 56 Fe values up to 1.6 ‰ Dauphas et al, 2004;Rouxel et al, 2005;Whitehouse and Fedo, 2007), although δ 56 Fe values for magnetite-rich bands from the c. 2.48-2.45 Ga Hamersley and Transvaal BIFs of Western Australia and South Africa, respectively, range from -1.0 ‰ to +1.2 ‰, with the average of 0.0 ‰ . Modern seafloor hydrothermal pyrite deposits have variable but mostly negative δ 56 Fe values ranging from -2.1 to -0.1 ‰, a wider range than that of seafloor-hydrothermal fluids defined at around -0.5 ± 0.3 ‰ (Rouxel et al, 2004Sharma et al, 2001;Beard et al, 2003) and, likely, reflecting variable kinetic and/or equilibrium isotope effect during pyrite precipitation pathways in hydrothermal conditions .…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of fractionation mechanisms of stable Fe isotopes is now well-advanced, and shows an overall range of ~5 ‰ in  56 Fe (for overview see Anbar, 2004;Beard and Johnson, 2004;Dauphas and Rouxel, 2006). The largest variability in the Fe isotope composition in any single type of sample has so far been measured in BIFs Dauphas et al, 2004Dauphas et al, , 2007Rouxel et al, 2005;Frost et al, 2007;Whitehouse and Fedo, 2007;Valaas Hyslop et al, 2008) and ranges from about -2.5 to 1.6‰ in  56 Fe. It has been shown that Fe isotope heterogeneities in BIFs can be preserved during diagenesis and metamorphism (Frost et al, 2007;Whitehouse and Fedo, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Dissimilatory Fe reduction appears to be a significant form of metabolism since at least 2.9 Ga (Vargas et al, 1998). In contrast, BIFs which are enriched in heavy Fe are regarded to reflect partial oxidation of Fe in the upper levels of ocean water (Dauphas et al, 2004;2007;Johnson and Beard, 2006;Johnson et al, 2008). The variability of stable Si isotope ratios has also been explored in natural systems, with an overall fractionation of ~12‰ in  30 Si (for overview see André et al, 2006;van den Boorn et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Firmas biológicas de particular interés son las asociadas a las llamadas Banded Iron Formations (i.e. Dauphas et al, 2004;Trendall y Blockley, 2004;Kappler et al, 2005;Konhauser et al, 2005;Koehler et al, 2010;Mloszewska et al, 2012) debido a su potencial antigüedad de ~4300 Ma (O'Neil et al, 2009).…”
Section: El Escenario De La Vida Tempranaunclassified